IMPLEMENTASI PEMBELAJARAN TEMATIK BERBASIS RAMAH ANAK PADA PESERTA DIDIK KELAS III DI MI KHADIJAH MALANG - Khusnun Nihayah; Fita Mustafida; Bagus Cahyanto (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This study aims to determine how the implementation of child-friendly-based thematic learning for third grade students at MI Khadijah Malang, and to determine the child-friendly-based thematic learning planning in grade III, implementation and assessment of thematic learning in grade III which is child-friendly. This type of research is a case study and uses a qualitative approach. How to collect data using interviews, observation, and documentation. The results of this study are as follows: 1) How is the planning of child-friendly based thematic learning for third grade students at MI Khadijah Malang 2) How is the implementation of child-friendly-based thematic learning for third grade students at MI Khadijah Malang 3) How is the thematic learning assessment child-friendly based on class III students at MI Khadijah Malang. The implication of infant-friendly-based thematic learning is to apply fun, anti-discriminatory, tolerant learning, provide a sense of security and based on Islam.